Spill the Tea: Fenomena Ghibah Virtual dalam Perspektif Islam dan Kewarganegaraan - Nurul Sidiqah; Syahidin Syahidin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The era of globalization brings changes that occur in society. Especially in the development of technology is now increasingly sophisticated which brings us to various conveniences, such as means of communication and the dissemination of information that is getting faster. The dissemination of information that is not accompanied by existing field facts will present various chaos in social media, one of which is the emergence of the Spill the Tea phenomenon which is a pronoun for gossip or gossip. This article aims to find out how the spill the tea phenomenon as a representation of virtual gossip in terms of Islam and citizenship. The method used in this research is literature study focusing on data or information related to the subject matter under study. Data collection through books or recent journals related to the research topic, then the data is analyzed descriptively to unravel the problem.